Upaya Peningkatan Hasil Belajar Melalui Model Pembelajaran Kooperatif Tipe Example Non Example - Nurlina Lase (JURNAL GLOBAL EDUKASI, 2018)
Abstract: This type of research is Classroom Action Research aims to improve and enhance learning activities that occur in the classroom. The object of research in this study is the application of example non example learning models to improve the quality and learning outcomes of students of Class VIII-A semester II (even) SMP Negeri 1 Gunungsitoli. In the first cycle, the average percentage of the implementation of learning activities of teacher respondents reached 65.38% and the results of the average percentage of questionnaire learning quality reached 61.82% and categorized as sufficient. In the second cycle, the average percentage of the implementation of learning activities of teacher respondents reached 81.73% and the results of the average percentage of questionnaire learning quality reached 79.65% and were categorized as good. While through the implementation of learning outcomes tests in the first cycle, the average learning outcomes reached 63.00 with a percentage of completeness of 54.29%. The implementation of the learning outcomes test in the second cycle obtained an average learning outcome of 78.00 with a percentage of completeness of 85.71%, so that the stated mastery of learning outcomes had reached a predetermined target. Keyword: Learning Outcomes, Example Non Example Abstrak: Jenis penelitian ini adalah Penelitian Tindakan Kelas (Classroom Action Research). bertujuan untuk memperbaiki dan meningkatkan kegiatan pembelajaran yang terjadi di kelas. Objek penelitian pada penelitian ini adalah penerapan model pembelajaran example non example untuk peningkatan kualitas dan hasil belajar siswa Kelas VIII-A semester II (genap) SMP Negeri 1 Gunungsitoli. Pada siklus I diperoleh rata-rata persentase pelaksanaan kegiatan pembelajaran responden guru mencapai 65.38% dan hasil rata-rata persentase angket kualitas pembelajaran mencapai 61.82% dan dikategorikan cukup. Pada siklus II diperoleh rata-rata persentase pelaksanaan kegiatan pembelajaran responden guru mencapai 81.73% dan hasil rata-rata persentase angket kualitas pembelajaran mencapai 79.65% dan dikategorikan baik. Sedangkan melalui pelaksanaan tes hasil belajar pada siklus I diperoleh rata-rata hasil belajar mencapai 63.00 dengan persentase ketuntasan sebesar 54.29%. Pelaksanaan tes hasil belajar pada siklus II diperoleh rata-rata hasil belajar sebesar 78.00 dengan persentase ketuntasan sebesar 85.71%, sehingga dinyatakan ketuntasan hasil belajar telah mencapai target yang telah ditentukan. Kata kunci: Hasil Belajar, Example Non Example